Identifikasi stunting pada anak balita di Desa Rantau Mapesai - Naila Fauza; Abdurrohman Abdurrohman; Ali Akbar Harahap; Ledy Monica; Lili Yani; Miftahul Jannah; Cici Mardila Purwanti; Syahrul Efendi Harahap; Ummi Sri Rahmadhani; Zulifa Febria (Unri Conference Series: Community Engagement, 2021)
Stunting is a condition of failure to thrive in children due to malnutrition for a long time. Thus, the child is shorter than normal children his age and has a delay in thinking. Generally caused by food intake that is not in accordance with nutritional needs. Stunting is a major nutritional problem in Indonesia. Stunting can be caused by lack of nutritious food intake, exclusive breastfeeding, low birth weight, and a history of infection. Stunting can have an impact on motor and verbal development, as well as an increase in degenerative diseases. The purpose of this study is to increase public knowledge about the dangers of stunting and how to prevent it. This activity was carried out in Rantau Mapesai Village, Rengat District, Indragiri Hulu Regency. The method used in this service activity is a qualitative method. Data obtained from interviews in the form of parents' last education level and family income. The data collection technique was carried out by observing the environment of the area affected by stunting and documenting during activities at the Melur Posyandu. Next is a literature study to collect data related to stunting from previous journals.